2021
DOI: 10.3390/s21041039
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Task End-to-End Self-Driving Architecture for CAV Platoons

Abstract: Connected and autonomous vehicles (CAVs) could reduce emissions, increase road safety, and enhance ride comfort. Multiple CAVs can form a CAV platoon with a close inter-vehicle distance, which can further improve energy efficiency, save space, and reduce travel time. To date, there have been few detailed studies of self-driving algorithms for CAV platoons in urban areas. In this paper, we therefore propose a self-driving architecture combining the sensing, planning, and control for CAV platoons in an end-to-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This Special Issue of Sensors aims at reporting on some of the recent research efforts on this increasingly important topic. The 12 accepted papers in this Issue cover vehicle position estimation [1], vehicle dynamic parameters estimation [2], cooperative collision warning systems [3], small object detection [4], impact identification of the driver's driving performance on executive control function [5], hybrid path planning for autonomous driving [6], trajectory tracking for autonomous driving [7], vehicle stability control [8], vehicle stability and ride comfort control [9], urban platooning protocol design for platoon [10], path planning algorithm for platooning [11], and self-driving architecture design for CAV platoon [12].…”
Section: About the Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue of Sensors aims at reporting on some of the recent research efforts on this increasingly important topic. The 12 accepted papers in this Issue cover vehicle position estimation [1], vehicle dynamic parameters estimation [2], cooperative collision warning systems [3], small object detection [4], impact identification of the driver's driving performance on executive control function [5], hybrid path planning for autonomous driving [6], trajectory tracking for autonomous driving [7], vehicle stability control [8], vehicle stability and ride comfort control [9], urban platooning protocol design for platoon [10], path planning algorithm for platooning [11], and self-driving architecture design for CAV platoon [12].…”
Section: About the Editorsmentioning
confidence: 99%
“…A self-driving architecture combining the sensing, planning, and control for CAV platoons in an end-to-end fashion is proposed in [12]. This multi-task model can switch between two tasks to drive either the leading or following vehicle in the platoon.…”
Section: About the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Navarro et al proposed sensor fusion-based E2E self-driving using real-world acquired data [15], but they did not analyze how to work their algorithm in real-world situations such as an urban traffic signal. Huch et al suggested V2X-based E2E self-driving for platooning [16]. Prashanth et al proposed JacintoNet, which was implemented in Texas Instruments (TI) TDA2x System on Chip, for real-time working [17].…”
Section: End-to-end Self-drivingmentioning
confidence: 99%
“…Actually, the mandatory safe distances for ordinary vehicles are generally no less than 50 m. For heavy-duty trucks, the requirement is usually longer than 100 m [ 13 ]. Promoted by the advanced 5G, V2X communication technologies [ 14 ], and autonomous driving technology [ 15 ], the following gap between vehicles can be shortened to less than 15 m [ 16 ]. Consequently, the transportation density will be significantly increased.…”
Section: Introductionmentioning
confidence: 99%